Damage detection of shear connectors based on power spectral density transmissibility - Li, Jun; Hao, Hong (Trans Tech Publications, 2013)
Damage of shear connectors in slab-on-girder structures will result in shear slippage between slab and girder, which significantly reduces the load-carrying capacity of the bridge. This paper proposes a dynamic damage detection approach to identify the damage of shear connectors in slab-on-girder bridges with power spectral density transmissibility (PSDT). PSDT formulates the relationship between the auto-spectral density functions of two responses. Measured impact force and acceleration responses from hammer tests are analyzed to obtain the frequency response functions at the slab and girder sensor locations by experimental modal analysis. When measurement data from the undamaged structure are available, PSDT from the slab response to the girder response is derived with the obtained frequency response functions. PSDT matrices in the undamaged and damaged states are directly compared to identify the damage of shear connectors. When the measurement data from the undamaged structure are not available, PSDT matrices from measured response at a reference sensor response to those of the slab and girder in the damaged state can also be used to detect the damage of shear connectors. Experimental studies with a concrete slab supported by two steel girders are conducted to investigate the accuracy and efficiency of the proposed approach. Identification results demonstrated that damage of shear connectors can be identified accurately and efficiently with and without measurement data from the undamaged structure.